Análise do discurso feminino entre casais violentos na cultura da agressão - Gnoato, Gilberto (2017)
This research work has as main objective the relational analysis in the studies of violent couples, proposing to interpret specifically the discursive constructions of middle-class women, with higher education and financial autonomy that, although being the target of physical and psychological violence, remain for long years living with their intimate partners. This category of women was chosen because of the vacuum that exists in the studies that investigate this type of population, since most of the studies on the phenomenon focus on low-income women, justifying that women's economic dependence as a result of their attachment to patriarchal power. As for the corpus of research, this comes from the reports of women allocated on the electronic website <wwwgilbertoresponde.com>. These are stories in the form of questions that seek a way out of the suffering of love. The website is designed by users as a self-help platform. Two other analyzes were also added to the corpus. The case study of Oliveira's autobiography (2011) and an interview with seven participants from the 2016 group of "Women Who Love Too Much Anonymous" (MADA). With the purpose of producing knowledge for practical application, aimed at solving problems Found in the daily reality, we opted for the modality of work called Applied Research (BARROS; LEHFELD, 2000; GIL, 2002). The Discourse Analysis according to Foucault (2012, 1986) was used as method and theoretical reference. In relation to the theoretical scope, this research was guided by the dialogue between Anthropology, Philosophy of Language, History, Sociology and contributions of Psychoanalysis. The violence of the couples is analyzed by the dialogical-relational perspective of Santos and Izumino (2005). One of the objectives is to problematize the dualism of certain feminist discourses that conceive of violence as an original and exclusive product of masculinity. The anthropologists Gregori (1993) and Machado (1998), for example, replace the polarization of violence hitherto unilaterally attributed to men to a relational form of understanding the phenomenon, through the study of "violent couples." On machismo, we adopt the premise of the psychologist Castañeda (2006) that neither machismo is a discourse exclusively of men nor violence a product exclusively of one of the poles of the relationship or individualized individual. Violence and machismo are not just concrete practices. It is a long process of microscopic socialization of Bourdieu's "symbolic domination" (2009: 138). Violence between couples is not located in a single place and/or individual, but is indented in what Foucault (1982, p244) defines as "devices." We select from the research corpus three devices that fuel violence. They are the device of "love-passion" in Rougemont (1988), of sexuality and machismo. These devices find fertile reverberation in the heart of a tremendously violent, emotional, hierarchical and paradoxical society such as Brazil (DAMATTA (1987; 1990; 1993). We also draw on Foucault's (1982) theoretical-political contributions on the power to understand violence as a "microphysics of violence" (FANINI, 1992; FOUCAULT, 1982;1984). Some of the results of this study indicate that the arguments of low income and lack of political awareness of women victims of violence have guided much of feminist research in the 1970s and 1980s. However, it is now known that violence against women. The woman "does not originate exclusively from economic class inequalities," according to Heilborn and Sorj (1999), neither of the lack of political awareness nor of its financial condition, considering the intense advances of women in the field of work and public life. Researches such as Grossi (1991), Gregori (1993), Santos and Izumino (2005) refer to practices of care for women beaten in the 1980s, since some feminist groups of the time attended to women victims of aggression conceived violence, often to a male production, when it is in reality a macroscopic phenomenon of the culture of aggression. Another aspect to emphasize regarding the care of victims of violence and feminist research is the little importance given to the discourse of passion-love (ROUGEMONT, 1998). Women expect much of the love (BOURDIEU, 2011, pp. 82-83) and depend more on it than men expect. If they are prisoners of the law of love, they are bound to virility and violence as a "burden" in Bourdieu's terms (2011, 64) intended to carry it. It is understood that between violent couples, it is as difficult for the woman to vacate the victim's place, as it is for the man, to leave the place of violence.